Justification of local anesthetic and choice of its concentration in composition of dental gel - Yu. S. Maslii; O. О. Hrudnytska; O. A. Ruban; G. V. Zaychenko (The State Expert Center of the Ministry of Health of Ukraine, 2019)
Dental diseases are often accompanied by painful sensations, so usually symptomatic treatment of these pathologies includes local anesthetics, as which we have selected anesthetic of local action - lidocaine hydrochloride. The aim of the research is to substantiate the rational concentration of lidocaine hydrochloride in the composition of the dental gel being developed by pharmacological screening of its model samples. The object of the study is dental gel with tincture "Phytodent" (PJSC "CPP "Red Star", Ukraine), choline salicylate 80% (Basf Pharma, Switzerland) and lidocaine hydrochloride (Societa Italiana Medicinali Scandicci, Italy). The anesthetic was injected into the gel at various concentrations - 1.0%, 1.5% and 2.0%. The study of local anesthetic/analgesic activity of gel test samples was performed by the Randall-Selitto method using an electronic Pressure Analgesiometer (IITC Life Science, USA). The study was conducted on male rats weighing 190-210 g. The animals were divided into three groups: animals of the 1st group were applied with 2.0% lidocaine hydrochloride gel (sample number 1), the second group - with 1.5% concentration (sample number 2), the third group - with 1.0% lidocaine content (sample number 3). The animal was held in the hands of a researcher, its limb was placed in analgesiometer. Determined the force of pressure in grams, which causes the reaction of the paw pull back / squeal in response to a painful stimulus. Analgesic activity was studied on the model of kaolin edema, which was simulated by sub-planar introduction of kaolin solution (10 mg/ml) in the amount of 0.1 ml/100 grams of body weight (administration under the aponeurosis of the posterior paw). In animals, the initial pain sensitivity was evaluated 1 hour after the introduction of the phlogogenic agent, after which the gel was applied to the foot, and in 1 hour 15 minutes, 1 hour 30 minutes and 2 hours after the exudative edema modelling. Calculated the percentage of change to the initial threshold of tactile sensitivity, as well as the percentage of change to the level of algesia (pain response) 1 hour after the introduction of the phlogogenic agent. Statistical processing of the data was performed using Student's t-criterion. According to the results, pronounced pain syndrome was detected in animals of all three groups 1 hour after the introduction of the phlogogenic agent. The use of gel with 1.0% concentration of lidocaine hydrochloride did not show a significant antinociceptive effect and could be considered as a tendency for analgesia. The pronounced local anesthetic effect was observed with the use of gel test specimens with the anesthetic concentrations of 1.5% and 2.0% after 15 and 30 minutes and lasted for at least 2 hours. The drug developed was compared with the dental gel "Kamistad®" (Stada Arzneimittel AG, Germany), which also contains lidocaine hydrochloride in an amount of 2.0%. Taking into account the fact that reliable statistical differences in the severity of analgesic activity between the test samples of gel number 1 and number 2 were not detected, it can be argued that lower lidocaine concentration 1.5% in the composition of the developed dental gel can be used. In addition, the claimed dental gel exceeded the referent drug "Kamistad®" (Stada Arzneimittel AG, Germany) by the expressiveness of antinociceptive effect.